Weight Gain and Blood Glucose Level in Granting Trans Fatty Acids (Study at Sprague Dawley) - S., Carmen; DK, Kusmiyati-Tjahjono (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2015)
Obesity was often cause by excessive food intake, lack of physical activities, genetic susceptibility, endocrine disorders, psychiatry disease. Pathogenesis DM type 2 was disturbance insulin or lack of insulin which result of genetic factor interaction, environment and life style changes. The life style changes were increasing the intake of fast foods, snack foods hydrogenated, the amount of consumption of fried foods, which turned out to contain trans fatty acids, causing obesity and diabetes mellitus type 2. How interaction with weight gain and level of blood glucose was unclearly. The result of study was analyzing effect of ALT against to weight gain and level of blood glucose. The study was experimental with randomized controlled group pretest posttest design, conducted at LPPT Unit IV UGM Yogyakarta. The sample was 30 male Sprague Dawley rat and aged 8 weeks, weight 200-300 grams and divided into 3 groups , were control group, group of Treatment I with ALT granting 5% and group of Treatment II with ALT granting 10% during 8 weeks, and weight and level of blood glucose checked. The parameter difference before and after the intervention was analyzed with Wilcoxon testing. ALT granting 5% and 10% during 8 weeks increase weight and blood glucose level significantly. In conclusion, the high dose of ALT increases weight and blood glucose.